Low dielectric constant series adjustable ltcc ceramic material, preparation method and application thereof
Patent Information
- Application Number
- CN202610947867.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-13
AI Technical Summary
本发明采用市面在售易获得的Al2O3作为基体,通过调控组分同样市面在售易获得、且熔融温度较低的BBS玻璃体系,可有效降低微波陶瓷材料烧结温度及介电常数,成本低,工程化简单,工程化管控性强;以Al2O3作为陶瓷填充材料,通过控制Al2O3、SiO2和BBS玻璃粉的比例,开发了一种介电常数系列可调的微波陶瓷材料体系;所得材料的介电常数在4.0~7.1较宽的范围内可调,且介电损耗可低至0.0010@1MHz、0.0004@10GHz,可按射频器件高频场景设计需求快速灵活地选择材料,可与不同的金属浆料进行匹配共烧;本发明的微波陶瓷材料具有相似的烧结特性,可在800~900℃间进行同一体系的多种介电常数介质与金属电极共烧且能避免微裂纹、层裂、翘曲等缺陷,可实现LTCC射频器件的集成设计。
Smart Images

Figure CN122897665A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials technology, and in particular to a series of tunable low dielectric constant LTCC ceramic materials, their preparation methods and applications. Background Technology
[0002] Currently, in highly realistic scenarios of the "Internet of Everything," the iterative advancements of 5G technologies—such as extremely high transmission speeds, extremely low latency, massive connection capacity, and minimal signal attenuation—have made LTCC (Low Temperature Co-fired Ceramics) technology, with its higher bandwidth, higher frequency, and better applicability, a strategic focus for countries in millimeter-band 5G applications and 6G deployments. LTCC, as a three-dimensional integrated technology combining microwave ceramic material technology, multilayer stacking fabrication technology, and multilayer circuit structure technology, can effectively achieve miniaturization, multilayering, integration, high performance, and high reliability of radio frequency devices. Microwave ceramic materials are the research hotspot and core of LTCC technology, and their performance directly determines the device performance and quality. In adapting LTCC microwave ceramic materials for 5G high-frequency applications and device integration, the following requirements must be met: ① LTCC microwave ceramic materials should have a lower dielectric constant (≤7) to reduce latency and increase signal transmission rate; ② Lower dielectric loss (≤0.0010@10GHz) to achieve good frequency selectivity and reduce device power consumption and heat generation; ③ A better coefficient of thermal expansion to match and co-fire with metal internal electrodes; ④ Higher ceramic density and near-zero temperature-frequency characteristics to adapt to the rapid and flexible iteration of LTCC RF devices. However, balancing miniaturization and high-frequency characteristics, heterogeneous co-firing of materials within the same system, and ensuring density remain key challenges for in-depth applications. When multiple materials with large differences in dielectric constants are integrated into RF modules, the differences in their coefficients of thermal expansion and sintering mechanisms can easily lead to problems such as microcracks, delamination, and cracking in LTCC RF devices.
[0003] LTCC microwave ceramic materials can be classified into three categories based on their composition: microcrystalline glass, ceramic + low-melting-point additives, and glass + ceramic. Microcrystalline glass exhibits excellent performance, but its preparation process requires extremely high precision, making commercialization difficult. Ceramic + low-melting-point additives are prone to performance degradation due to the addition of low-temperature sintering aids, leading to unstable dielectric constants and increased dielectric loss. In contrast, the glass + ceramic system, through the composite of low-softening-point glass and ceramic materials, effectively lowers the sintering temperature, has a simple preparation process, and its dielectric properties are easily adjustable and controlled, thus becoming a hot topic in research and engineering in recent years. In recent years, the industry has also conducted some research and exploration on a series of tunable low-dielectric-constant, low-loss LTCC microwave ceramic materials. In related technologies, the dielectric constant of the LTCC substrate in patent CN109775993A can be adjusted within a certain range of 4.3-6.0. However, the dielectric constant range of this solution is relatively narrow, and the dielectric loss is relatively high (minimum 0.0020@1MHz, 0.0032@10GHz), and the porosity is also relatively high (minimum 0.11%). This has certain limitations in high-frequency applications such as 10GHz for RF devices. For example, LTCC high-pass filters (HF3216, 8.56-12.8GHz) require low-loss microwave ceramic materials with a dielectric constant of approximately 6.8. In patent CN111302792A, the dielectric constant of the low-temperature co-fired dielectric material can be adjusted within a relatively wide range of 7.0-12.0, but the dielectric constant is relatively high, with a minimum of only 7. This affects latency in high-frequency applications, thus affecting signal transmission rate. The dielectric constant of LTCC material in patent CN112624617A can be adjusted within a wide range of 5.40-9.85, but the dielectric constant of its scheme is still relatively large, and it is a microcrystalline glass system, which is difficult to engineer. For example, the dielectric constant of the microwave ceramic material used in the design of LTCC bandpass filter (BF3216, 17.7-21.2GHz) is about 4.0.
[0004] Therefore, it is essential to develop LTCC microwave ceramic materials based on the same material system, with low dielectric constants that are tunable over a wide range, low dielectric loss, and easy engineering control. This would allow for the rapid and flexible fulfillment of the requirement for more choices of single dielectric constant materials in high-frequency applications, while avoiding the quality and reliability issues that arise when integrating multiple materials with large dielectric constants into LTCC RF devices. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a series of tunable low dielectric constant LTCC ceramic materials, their preparation methods and applications.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a series of tunable low dielectric constant LTCC ceramic materials, comprising, by mass percentage, 35%~55% BBS glass powder, 35%~55% Al2O and 0%~60% SiO2.
[0007] This invention prepares a series of low dielectric constant and low loss Al2O3+ glass system microwave ceramic materials based on the same Al2O3+ glass material system. These materials can be quickly and flexibly selected according to the design requirements of high-frequency scenarios to achieve the miniaturization and integration of subsequent radio frequency devices. They also have good high-frequency performance and can be co-fired with different metal pastes. The LTCC ceramic materials formulated in this invention have a series of adjustable low dielectric constants over a wide range and low loss, which solves the problems of microcracks, warping, and cracking that easily occur when radio frequency devices are co-fired with different systems.
[0008] This invention combines the performance requirements of radio frequency devices with engineering needs, employing an Al2O3+glass system. Al2O3 has a low dielectric constant of 9-10, resulting in a dielectric loss as low as 5×10⁻⁶. -5 With a sintering temperature as high as 1600℃, the glass system mainly uses relatively solidified BBS low-softening-point borosilicate glass to reduce the sintering temperature and dielectric constant. Simultaneously, crystalline SiO2 is added to adjust the dielectric properties and porosity. Through mixed doping and formulation of these three components, a microwave ceramic material with an adjustable dielectric constant within a wide range of 4.0~7.1, dielectric loss as low as 0.0010@1MHz and 0.0004@10GHz, and porosity as low as 0.08% is prepared. It exhibits excellent high-frequency performance, good ceramic body density within the 800℃~900℃ temperature range, and is low-cost and easily controlled. This material can be widely used in high-frequency fields, such as high-frequency multilayer inductors, filters, duplexers, and integrated modules in LTCC RF devices.
[0009] As a preferred embodiment of the LTCC ceramic material of the present invention, the LTCC ceramic material comprises, by mass percentage, 35%~55% BBS glass powder, 25%~45% Al2O3, and 0%~35% SiO2. The dielectric loss of the LTCC ceramic material within this content range is less than 0.0010@10GHz, indicating even lower dielectric loss.
[0010] In a preferred embodiment of the LTCC ceramic material of the present invention, the LTCC ceramic material comprises, by weight percentage, 45%~55% BBS glass powder, 25%~45% Al2O3, and 0%~25% SiO2. LTCC ceramic materials with this content have lower porosity.
[0011] In a preferred embodiment of the LTCC ceramic material of the present invention, the LTCC ceramic material comprises, by mass percentage, 45% BBS glass powder, 35% Al2O3, and 20% SiO2. This content results in the lowest dielectric loss and lowest porosity for the LTCC ceramic material.
[0012] In a preferred embodiment of the LTCC ceramic material of the present invention, the Al2O3 is high-purity α-Al2O3; the SiO2 is crystalline SiO2. High purity means that the Al2O3 content is not less than 99.99% (4N).
[0013] In a preferred embodiment of the LTCC ceramic material of the present invention, the BBS glass powder comprises the following components by mass percentage: 40%~65% SiO2, 22%~48% H3BO3, 6%~12% BaCO3, 0%~4% CaCO3, 0.3%~0.8% Na2CO3, 0.2%~1.0% K2CO3, 0.8%~1.8% Al2O3, 0.6%~0.9% MgO, and 0.5%~1.1% TiO2. The present invention utilizes a BBS glass composition formulation with a low softening point to achieve the preparation of microwave ceramic materials with a sintering temperature below 900℃, a low dielectric constant ≤7.1, and a porosity as low as 0.08%.
[0014] As a preferred embodiment of the LTCC ceramic material of the present invention, the BBS glass powder comprises the following components by mass percentage: 55.93% SiO2, 24.67% H3BO3, 11.81% BaCO3, 3.06% CaCO3, 0.39% Na2CO3, 0.64% K2CO3, 1.63% Al2O3, 0.80% MgO and 1.07% TiO2.
[0015] As a preferred embodiment of the LTCC ceramic material of the present invention, the total molar content of K and Na in the BBS glass powder is ≤1.25 mol%, and the total molar content of Ca and Ba is ≤8.6 mol%, which can better control the degradation of the dielectric properties of the ceramic material and reduce the porosity.
[0016] As a preferred embodiment of the LTCC ceramic material of the present invention, the method for preparing the BBS glass powder includes the following steps: S1. Mix all the raw materials of BBS glass powder, and mix them evenly by wet ball milling. Dry and crush the slurry after ball milling to obtain premixed powder. S2. After melting and quenching the premixed powder, it is then wet-milled to control the powder particle size D50≤2.5μm. The slurry after ball milling is dried to obtain BBS glass powder.
[0017] In a preferred embodiment of the LTCC ceramic material of the present invention, in step S1, the medium for wet ball milling includes anhydrous ethanol and ZrO2 balls, and the wet ball milling is performed using a planetary ball mill; the wet ball milling time is 1~1.2h.
[0018] In a preferred embodiment of the LTCC ceramic material of the present invention, the drying temperature in step S1 is 70~75°C.
[0019] In a preferred embodiment of the LTCC ceramic material of the present invention, the melting temperature in step S2 is 1250~1350℃.
[0020] In a preferred embodiment of the LTCC ceramic material of the present invention, in step S2, the quenching is performed using a glass rolling mill with a double roller spacing of 0.1~0.2 mm and a rotation speed of 6~8 r / min.
[0021] In a preferred embodiment of the LTCC ceramic material of the present invention, in step S2, the medium for wet ball milling includes anhydrous ethanol and ZrO2 balls, and the wet ball milling time is 8-10 hours.
[0022] Secondly, the present invention provides a method for preparing the LTCC ceramic material, wherein BBS glass powder, Al2O3 and SiO2 are mixed in proportion, wet ball milling is performed, the slurry after ball milling is dried, and powder is obtained to obtain the LTCC ceramic material.
[0023] In a preferred embodiment of the preparation method described in this invention, the medium for wet ball milling is zirconium balls and anhydrous ethanol, and the rotation speed of the wet ball milling is 200 r / min.
[0024] Thirdly, the present invention provides the application of the above-mentioned LTCC ceramic material in the fabrication of radio frequency devices.
[0025] Fourthly, the present invention provides a radio frequency device prepared using the aforementioned LTCC ceramic material.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention uses commercially available Al2O3 as the matrix. By controlling the composition of a BBS glass system, which is also commercially available and has a lower melting temperature, the sintering temperature and dielectric constant of microwave ceramic materials can be effectively reduced. This results in low cost, simple engineering, and strong engineering control. Using Al2O3 as the ceramic filler, a series of microwave ceramic material systems with adjustable dielectric constants are developed by controlling the ratio of Al2O3, SiO2, and BBS glass powder. The dielectric constant of the resulting material is adjustable in a wide range of 4.0 to 7.1, and the dielectric loss can be as low as 0.0010@1MHz and 0.0004@10GHz. The material can be quickly and flexibly selected according to the design requirements of high-frequency RF devices and can be co-fired with different metal pastes. The microwave ceramic material of this invention has similar sintering characteristics and can be co-fired with metal electrodes of various dielectric constants in the same system at 800~900℃, avoiding defects such as microcracks, delamination, and warping. This enables the integrated design of LTCC RF devices. Attached Figure Description
[0027] Figure 1 The images shown are cross-sectional SEM images of LTCC ceramic materials sintered at 875°C in the examples and comparative examples of Test Example 1 of this invention. a is Comparative Example 1, b is Comparative Example 3, c is Example 2, d is Example 8, e is Example 11, and f is Example 7. Figure 2 The simulated structure, actual sample, and internal co-fired morphology with silver of the 3216-type LTCC low-pass filter (LF3216, 2.25 GHz) prepared in Test Example 2 of this invention are shown. Figure 3 The above are the measured performance results of the 3216 type LTCC low-pass filter (LF3216, 2.25 GHz) sample prepared from LTCC ceramic material in Example 2 of this invention. Detailed Implementation
[0028] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0029] Unless otherwise specified, all other materials and reagents used in the examples are commercially available.
[0030] Examples 1-13 This invention discloses a series of tunable low dielectric constant LTCC ceramic materials, comprising, by mass percentage, 35%~55% BBS glass powder, 5%~55% Al2O3, and 0%~60% SiO2. The Al2O3 is high-purity α-Al2O3; the SiO2 is crystalline SiO2.
[0031] The BBS glass powder comprises the following components by mass percentage: 40%~65% SiO2, 22%~48% H3BO3, 6%~12% BaCO3, 0%~4% CaCO3, 0.3%~0.8% Na2CO3, 0.2%~1.0% K2CO3, 0.8%~1.8% Al2O3, 0.6%~0.9% MgO, and 0.5%~1.1% TiO2.
[0032] The preparation method of the BBS glass powder includes the following steps: (1) Mix all the raw materials of BBS glass powder, put them into a nylon can, add anhydrous ethanol and ZrO2 balls, and then mix them evenly in a planetary ball mill for 1 hour. The slurry after ball milling is discharged and placed in a 70℃ oven to dry. The dried solid is crushed evenly to obtain premixed powder. (2) Pour the premixed powder into an Al2O3 crucible, then heat it to 1250℃ in a silicon molybdenum rod furnace to melt it. Quench it through a glass rolling mill with a double roller gap of 0.1~0.2 mm and a rotation speed of 6~8 r / min to obtain sheet glass. Crush the obtained sheet glass and place it in an Al2O3 ball mill jar. Add ZrO2 balls and anhydrous ethanol, and ball mill for 8~10 h. Control the powder particle size D50≤2.5μm. Discharge the ball-milled slurry and dry it to obtain BBS glass powder.
[0033] The preparation method of the LTCC ceramic material is as follows: BBS glass powder, Al2O3 and SiO2 are mixed in proportion, poured into a nylon can, zirconium balls and an appropriate amount of anhydrous ethanol are added, and the mixture is ball-milled at 200 rpm for 30 min to obtain a slurry. The slurry is then dried in an oven at 70℃ for 12 h and then powdered to obtain the LTCC ceramic material.
[0034] Examples 1-13 are 13 examples of the LTCC ceramic material of the present invention, and Comparative Examples 1-4 are 4 comparative examples of the LTCC ceramic material of the present invention.
[0035] Table 1 shows the BBS glass powder, Al2O3, and SiO2 content information of the LTCC ceramic materials in Examples 1-13 and Comparative Examples 1-4. Table 1 The composition and content of the BBS glass powder in Examples 1-13 can be finely adjusted within the above range as required to achieve the dielectric properties required for LTCC ceramic materials. The composition and content of the BBS glass powder in Examples 5, 10, 11, 13 and Comparative Examples 1-4 are shown in Table 2. The composition and content of the BBS glass powder in Comparative Examples 1-4 are the same as those in Example 13. Table 2 Test Example 1 The dielectric constant, dielectric loss, and porosity of the LTCC ceramic materials in the examples and comparative examples were tested.
[0036] In Examples 1-13 and Comparative Examples 1-4, 8% PVA solution was added to the LTCC ceramic materials. After granulation and sieving, the materials were pressed into Φ16×2 mm discs and sintered in a box furnace according to the following temperature profile: heating at 2℃ / min to 500℃, holding for 60 min, then heating at 5℃ / min to 875℃, holding for 30 min, and cooling with the furnace to obtain disc samples. After silver coating on both sides of the discs, they were placed in a box furnace, and the silver firing profile was: heating at 10℃ / min to 560℃, holding for 10 min, and cooling with the furnace to obtain disc samples suitable for dielectric performance testing at 1MHz.
[0037] In Examples 1-13 and Comparative Examples 1-4, 8% PVA solution was added to the LTCC ceramic materials. After granulation and sieving, the materials were pressed into Φ16×10 mm cylinders under a pressure of 200 MPa. The cylinders were then placed in a box furnace and sintered according to the temperature curve: the temperature was increased to 500℃ at 1℃ / min and held for 120 min, then increased to 875℃ at 3℃ / min and held for 60 min. After cooling in the furnace, cylindrical samples suitable for dielectric performance testing under 10 GHz conditions were obtained.
[0038] The dielectric constant and dielectric loss of the wafer samples under 1 MHz conditions were calculated using the parallel plate capacitance method with an LCR meter from KEYSIGTH, USA.
[0039] The dielectric constant and dielectric loss of the cylindrical sample at 10 GHz were measured using a network analyzer from KEYSIGTH in the United States according to the Hakki-Coleman method (i.e., dielectric resonator method).
[0040] The porosity was calculated using a German ZEIS scanning electron microscope with Avizo analysis of the disc samples.
[0041] Scanning electron microscopy (SEM) was used to observe the cross-sectional SEM image of LTCC ceramic material sintered at 875℃.
[0042] The test results of dielectric constant, dielectric loss and porosity of LTCC ceramic materials in Examples 1-13 and Comparative Examples 1-4 are shown in Table 3. Table 3 SEM images of the cross-sections of LTCC ceramic materials sintered at 875°C in the examples and comparative sections are shown below. Figure 1 As shown, a is Comparative Example 1, b is Comparative Example 3, c is Example 2, d is Example 8, e is Example 11, and f is Example 7.
[0043] Table 3 and Figure 1 The results show that the LTCC ceramic material of the present invention can achieve a series of adjustable dielectric constants between 4.0 and 7.1 by adjusting the ratio of BBS glass powder, Al2O3, and SiO2, with dielectric losses as low as 0.0010@1MHz and 0.0004@10GHz, and a porosity as low as 0.08%, all of which meet the dielectric performance requirements of radio frequency devices used in high-frequency scenarios. Among them, Example 7 has a dielectric constant of 5.2, the lowest dielectric loss (0.0010@1MHz and 0.0004@10GHz), and the lowest porosity (0.08%); Example 8 has the highest dielectric constant (7.1), dielectric losses (0.0015@1MHz and 0.0009@10GHz), and a porosity of 0.22%; Example 11 has the lowest dielectric constant (4.0), dielectric losses (0.0014@1MHz and 0.0010@10GHz), and a porosity of 0.78%.
[0044] In Comparative Examples 1-2, the BBS glass powder content in the LTCC ceramic materials was too high (60%) or too low (30%), and in Comparative Examples 3-4, the Al2O3 content was too high (60%) or too low (0%), with porosity exceeding 1%, resulting in significant degradation of dielectric loss and making it difficult to apply to high-frequency applications. Therefore, to meet the requirements of stable and dense sintering, the ratio of BBS glass powder, Al2O3, and SiO2 needs to be controlled within the following range: BBS glass powder 35%~55wt%, Al2O3 5%~55wt%, and SiO2 0%~60wt%.
[0045] Meanwhile, within the specified content range, the porosity of BBS glass powder generally decreased with increasing content, and remained below 1%, effectively controlling the porosity. In Comparative Example 1, excessive BBS glass powder resulted in low viscosity at high temperatures, the highest porosity (3.51%), sample warping, and a significant increase in dielectric loss. In Comparative Example 3, the excessive Al2O3 content made it difficult for the glass liquid phase to encapsulate the high proportion of Al2O3 particles, resulting in a porosity of 1.89% and a significant increase in dielectric loss. Compared to Comparative Example 1, in Example 2, the BBS glass powder content was reduced to 55%, the Al2O3 content was increased, and the SiO2 content was reduced to adjust the dielectric properties, resulting in an increased dielectric constant, reduced dielectric loss, and a significant reduction in porosity (only 0.10%). Compared to Example 2, Example 2... Example 8 further reduced the BBS glass powder content and increased the Al2O3 content to 55%, achieving a maximum dielectric constant of 7.1, further reducing dielectric loss, and slightly increasing porosity to 0.22%. Compared to Example 8, Example 11 simultaneously reduced the BBS glass powder and Al2O3 content and increased SiO2 to 60%, achieving a minimum dielectric constant of 4.0. Due to the lower BBS glass powder content, the porosity increased to 0.78%. In Example 7, the BBS glass powder, Al2O3, and SiO2 achieved a more favorable ratio, with a dielectric constant of 5.2, the lowest dielectric loss, and the lowest porosity.
[0046] Test Example 2 In Examples 1-13, appropriate amounts of binary or ternary solvents, KD13 dispersant, PVB binder, DOP plasticizer, and defoamer were added to the LTCC ceramic materials, and the mixture was slowly milled in a ball mill for approximately 24 hours to obtain a cast slurry. According to the design requirements of RF devices, samples were processed through casting, screen printing, lamination, sintering, waist sealing, end sealing, and surface treatment, and then subjected to electrical performance testing.
[0047] The electrical performance parameters of the RF devices, such as insertion loss, out-of-band rejection, and return loss, were tested using a KEYSIGTH network analyzer and its matching fixtures (USA). The low-frequency impedance of the RF devices was measured using a WAYNE KERR precision impedance meter (UK).
[0048] Test results show that the radio frequency devices prepared from the LTCC ceramic materials in Examples 1-13 can be used at frequencies up to 100 GHz.
[0049] Among them, using LTCC ceramic material with a dielectric constant of 5.4 and losses of 0.0020@1MHz and 0.0010@10GHz from Example 2, the simulated structure, actual sample, and internal co-fired morphology of a 3216 type LTCC low-pass filter (LF3216, 2.25 GHz) prepared according to the above process are shown in the figure. Figure 2 As shown.
[0050] The measured performance results of the 3216-type LTCC low-pass filter (LF3216, 2.25 GHz) sample prepared from LTCC ceramic material in Example 2 are as follows: Figure 3 As shown, the results indicate that the sample has a center frequency of 2250MHz, a return loss of ≥14dB@DC~2250MHz, an insertion loss of ≤1.3dB@DC~2250MHz, and out-of-band rejection of ≥27dB@2850MHz and ≥20dB@7800MHz, meeting the design requirements.
[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A series of tunable low dielectric constant LTCC ceramic materials, characterized in that, By weight percentage, it includes 35%~55% BBS glass powder, 35%~55% Al2O and 0%~60% SiO2.
2. The LTCC ceramic material as described in claim 1, characterized in that, The Al2O3 is high-purity α-Al2O3; the SiO2 is crystalline SiO2.
3. The LTCC ceramic material as described in claim 1 or 2, characterized in that, The BBS glass powder comprises the following components by mass percentage: 40%~65% SiO2, 22%~48% H3BO3, 6%~12% BaCO3, 0%~4% CaCO3, 0.3%~0.8% Na2CO3, 0.2%~1.0% K2CO3, 0.8%~1.8% Al2O3, 0.6%~0.9% MgO, and 0.5%~1.1% TiO2.
4. The LTCC ceramic material as described in claim 3, characterized in that, The total molar content of K and Na in the BBS glass powder is ≤1.25 mol%; And / or, the total molar content of Ca and Ba in the BBS glass powder is ≤8.6 mol%.
5. The LTCC ceramic material as described in claim 3, characterized in that, The preparation method of the BBS glass powder includes the following steps: S1. Mix all the raw materials of BBS glass powder, and mix them evenly by wet ball milling. Dry and crush the slurry after ball milling to obtain premixed powder. S2. After melting and quenching the premixed powder, it is then wet-milled to control the powder particle size D50≤2.5μm. The slurry after ball milling is dried to obtain BBS glass powder.
6. The LTCC ceramic material as described in claim 5, characterized in that, In step S1, the media used in the wet ball milling include anhydrous ethanol and ZrO2 balls, and the wet ball milling is performed using a planetary ball mill; the wet ball milling time is 1~1.2h. And / or, in step S1, the drying temperature is 70~75°C.
7. The LTCC ceramic material as described in claim 5, characterized in that, In step S2, the melting temperature is 1250~1350℃; And / or, in step S2, the quenching is performed using a glass rolling mill, wherein the distance between the two rollers of the glass rolling mill is 0.1~0.2mm and the rotation speed is 6~8r / min; And / or, in step S2, the medium for wet ball milling includes anhydrous ethanol and ZrO2 balls, and the wet ball milling time is 8~10h.
8. A method for preparing the LTCC ceramic material according to any one of claims 1 to 7, characterized in that, BBS glass powder, Al2O3 and SiO2 are mixed in a certain proportion, wet ball milled, the slurry after ball milling is dried and powdered to obtain LTCC ceramic material.
9. The use of the LTCC ceramic material according to any one of claims 1 to 7 in the fabrication of radio frequency devices.
10. A radio frequency device, characterized in that, It is prepared using the LTCC ceramic material according to any one of claims 1 to 7.
Citation Information
Patent Citations
LTCC substrate and preparation method thereof
CN109775993A
Dielectric constant series adjustable low-temperature co-fired dielectric material and preparation method thereof
CN111302792A
Dielectric constant series adjustable glass powder for low-dielectric-constant LTCC material and preparation method of glass powder
CN112624617A